2021
DOI: 10.1080/1389224x.2021.1880453
|View full text |Cite
|
Sign up to set email alerts
|

Gender, place, and agricultural extension: a mixed-methods approach to understand farmer needs in Liberia

Abstract: Purpose: This study explores the intersection of gender and place with agricultural extension services to understand disparities in resource and information access and build community resilience in post-conflict Liberia. It emphasizes how such intersections may be further compounded by climate change and provides possible solutions. Methodology: Using a community-based research approach, 352 surveys and 44 focus groups were conducted in 22 communities in 3 counties in north-central Liberia. Subsequently, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The Chi-square analysis indicate that there is a significant relationship between agricultural extension services (χ2 = 19.628; df = 1; p = 0.000). This finding agrees with Williams and Taron (2020) and Forbang et al (2019) who observed gender disparity in accessing agricultural extension service delivery. To a great extent, female agricultural extension agents are few in the study locale.…”
Section: Gender and Access To Extension Agents And Servicessupporting
confidence: 92%
See 3 more Smart Citations
“…The Chi-square analysis indicate that there is a significant relationship between agricultural extension services (χ2 = 19.628; df = 1; p = 0.000). This finding agrees with Williams and Taron (2020) and Forbang et al (2019) who observed gender disparity in accessing agricultural extension service delivery. To a great extent, female agricultural extension agents are few in the study locale.…”
Section: Gender and Access To Extension Agents And Servicessupporting
confidence: 92%
“…To a great extent, female agricultural extension agents are few in the study locale. Respondents cited comfort when extension agent of the same gender delivers extension services as supported by Williams and Taron (2020) who indicated the same scenarios in agricultural extension services. A female farmer remarked in an FGD discussion that:…”
Section: Gender and Access To Extension Agents And Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Women have poor access to training, extension services, and technology necessary for effective adaptation to the impacts of climate change (Witinok-Huber et al, 2021). Moreover, constraints to technology adoption among women are evident across stages of technology adoption, which include awareness, testing, and continued adoption (Oyetunde- Usman et al, 2021).…”
Section: Impact On Agricultural Productionmentioning
confidence: 99%